Investigating The Environmental Impacts Of Different Approaches Of Agricultural Waste Management Using Ahp Technique - Khodkam Himan; Pourdarbani Razieh; Ghaebi Hadi; Hernandez-Hernandez Mario (Acta Technologica Agriculturae)
Environmental problems and the ever-increasing growth of population dictate the need for new methods to turn the problem into an opportunity. The recycling of agricultural waste is very important to achieve sustainable development of agriculture. Present paper focuses on how the proper disposal and recycling of agricultural waste can significantly reduce greenhouse gas emissions, conserve resources, and improve soil fertility. Hereupon, the specified criteria were determined by relevant organisations. Five final products including composting, biochar, biogas, reuse/recycling, and incineration resulting from the technologies used were investigated using the AHP technique. In addition to the effective management of agricultural waste, these technologies help in the production of electricity, fertiliser, and carbon absorption, which results in the reduction of climate change and the reduction of economy. Among the proposed products, biochar was preferred, and the incineration method was ranked the last. Biochar offers potential environmental benefits in terms of reducing greenhouse gas emissions, increasing the quality and quantity of agricultural products, and preventing soil erosion and degradation as well as water pollution. High rank was assigned to environmental criteria, and the actual waste production sub-criterion was preferred over other criteria with a weight of 0.170. The lowest weight was obtained for the shipping distance (weigh = 0.013).